Pengembangan Media Pembelajaran Interaktif Rumbi untuk Meningkatkan Kemampuan Membaca Kata pada Peserta Didik Disabilitas Intelektual Ringan - Yulianti, Sri Aulia; Taufan, Johandri; Damri, Damri; Mahdi, Arisul; Zulpiani, Mardhatillah (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The development of the interactive learning media RUMBI is expected to facilitate teachers in delivering reading materials more optimally, as well as to adjust to the learning needs of students with mild intellectual disabilities. This study aims to assess the validity and practicality of the interactive learning media RUMBI as a supporting tool in improving word reading skills for students with mild intellectual disabilities. The approach used in this research is Research and Development (R&D) with modifications from the development model proposed by Borg and Gall. Data were collected through observation and interview techniques, then analyzed descriptively qualitatively based on expert evaluations. According to the validation test results, RUMBI media achieved validation scores of 94% from content experts, 100% from language experts, and 96% from media experts. These results indicate that this media falls into the very valid category and is suitable for use in teaching word reading to students with mild intellectual disabilities.